Equrna 1989. - Galerija Equrna, Ljubljana (Ljubljana : Galerija Equrna, 1989)
Bernard, Emerik ; Brdar, Jakov ; Gorenec, Bojan ; Gruden, France ; Gvardjancic, Herman ; Huzjan, Zdenko ; Kapus, Sergej ; Kemperle, Bozo ; Kirbis, Dusan ; Krasovec, Metka ; Logar, Lojze ; etc.
boek